2019
DOI: 10.1371/journal.pone.0222697
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NF-κB- and STAT1-mediated plasmacytoid dendritic cell functions by A20

Abstract: Dendritic cells (DCs) are professional antigen presenting cells involved in the induction of T cell-mediated adaptive immunity. Plasmacytoid DCs (pDCs) originate from lymphoid precursors and produce type I interferons (IFNs) in response to pathogens. A20 is considered as a negative regulator of toll-like receptor (TLR) signaling pathways, in which Toxoplasma gondii- derived profilin (TgPRF) is a TLR11/12 ligand recognised by DCs to stimulate their maturation/activation. Little is known about contributions of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…37 Moreover, some new strategies could suppress IκB activity via increasing IκB protein degradation. 38,39 Similarly, our results revealed that IκB was suppressed from transferring into the nucleus under the effect of nobiletin on BC cells.…”
Section: Discussionsupporting
confidence: 67%
“…37 Moreover, some new strategies could suppress IκB activity via increasing IκB protein degradation. 38,39 Similarly, our results revealed that IκB was suppressed from transferring into the nucleus under the effect of nobiletin on BC cells.…”
Section: Discussionsupporting
confidence: 67%
“…Although it is well known that A20 participates in inhibiting functional activation of several immune cells including dendritic, T and B cells (Duy et al, 2019;Hovelmeyer et al, 2011), the effect of A20 on PBMC function is not mentioned yet. In addition to the presence of dendritic, T and B cells, PBMCs also comprise of other cell types such as myeloid, NK cells and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The cell migration is characterized by binding between chemokine receptors on the cell surface to specific ligands expressed on epithelial cells in lymphoid organs. A20 has been shown to inhibit the migration of cancer cells mediated through activation of NF-κB and signal transducer and activator of transcription (STAT) signalings (Chen et al, 2018;Duy et al, 2019). In order to maintain tissue homeostasis, the immune cells eventually undergo cell apoptosis, which is identified by activation of caspases and exposure of phosphatidylserine (PS) on the external leaflet of the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of A20 or CYLD in mouse immune cells results in constitutive activity of several pathways, including nuclear factor kappalight-chain-enhancer of activated B cells (NF-κB) and signal transducer and activator of transcriptions (STATs). 6,7 In humans, inactivation of A20 leads to the progression of lymphomas by inducing the proliferation of lymphoma cells. 8,9 Mutations in exon 3 of A20 gene cause the risk of malignant T-cell acute lymphoblastic leukemia (T-ALL) 10 and chronic lymphocytic leukemia (CLL).…”
Section: Introductionmentioning
confidence: 99%